A case study of Elphinstone Road foot-over-bridge stampede in Mumbai. (24th February 2020) - Kadam, Sanjeev; Bandyopadhyay, Prabir Kumar
Planning or implementation delays of critical infrastructure (CI) projects resulted in misfortunes such as accidents, stampedes or deaths. In this descriptive case study, an incidence of the stampede at the suburban train station in Mumbai has discussed. An endeavour has been made to examine underlying causes which instigate direct causes reinforced by contributing causes. Indian Army was being roped in for constructing additional foot-over-bridge (FOB) after the stampede. This case features the earnestness of appropriate and timely development of associated infrastructure in and around suburban stations in Mumbai proportionate to abundant passengers commuting. Post stampede reports from newspapers, televisions channels and the internet have largely used to build this case. Pre and post cause analysis discussion on Elphinstone Road FOB stampede case is an eye-opener to justify sustainable emergency management and associated infrastructure development in Mumbai.